(untitled) (Tzintzun, Revista de Estudios Históricos, 2022)
Between 1711 and 1713 the Inquisition of Cartagena de Indias prosecuted Magdalena Hodston, a female of “English nation”, who settled down in that port city, generating great questions. Her case is significant because there are no studies on the subject. In this sense, her case will allow us to reflect not only on her life story, but also on the religious control exercised by the Inquisition and the mobility of Protestant women in the Hispanic dominions, which is framed in the diplomatic relations of the Spanish Monarchy with other kingdoms.